Investigating the Pozzolanic Properties of Canarium schweinfurthii (‘Atili’) Seed Shell Ash as Partial Replacement for Cement in Concrete - Ikechelu, Ifeanyi Macsylva; Wilson, Uwemedimo Nyong; Mohammed, Isa Sani; Odeyemi, Samson Olalekan; Eze, Okereke Chika (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
Ethnomedicinal, insecticidal, biological and other non-engineering uses of Canarium seed have been identified but little or no engineering uses have been explored. This research investigates the effect of Canarium schweinfurthii Seed shell Ash (CSSA) on the mechanical properties of concrete. CSSA was obtained after calcination of Canarium schweinfurthii seed shell at 4000C, 7000C and 1000 0C. X-ray Florescence (XRF) analysis carried out revealed the best sample of CSSA to be used for this work, and found to be a Class C pozzolana, which contains 51.21% of (SiO2 + Al2O3 + Fe2O3). The compressive and flexural strengths were determined at 7, 14, 21 and 28 days. The workability of the concrete was found to have dropped with the increment in the percentage of CSSA in the concrete. The compressive strength and flexural strength of the concrete cubes declined with the increment in the percentage of CSSA in the concrete. The compressive strength of the CSSA concrete after each curing age for the control and all the different percentages of CSSA replacement all met the minimum requirement for the characteristic strength (20 N/mm2). From the result, the reduction in compressive strength of the concrete at 28 days is between 0% and 5%, with the optimal increment in the strength achieved at 10% CSSA. The flexural strength of the CSSA concrete reduces drastically with increment in the CSSA content across all the curing ages, having an optimal replacement at 5% CSSA replacement.